Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\frac{x-1}{21}=\frac{3}{x+1}\)
=> \(\left(x-1\right)\left(x+1\right)=21\cdot3\)
=> \(x^2-1=63\)
=> \(x^2=64\)
=> \(\orbr{\begin{cases}x^2=8^2\\x^2=\left(-8\right)^2\end{cases}\Rightarrow}\orbr{\begin{cases}x=8\\x=-8\end{cases}}\)
\(2\frac{7}{9}-\frac{12}{13}x=\frac{7}{9}\)
=> \(\frac{12}{13}x=2\)
=> \(x=\frac{13}{6}\)
d, \(\frac{x-1}{21}=\frac{3}{x+1}\)
\(\Leftrightarrow\left(x-1\right)\left(x+1\right)=63\)
\(\Leftrightarrow x^2-1=63\Leftrightarrow x^2=64\Leftrightarrow x=\pm8\)
e, \(2\frac{7}{9}-\frac{12}{13}x=\frac{7}{9}\)
\(\Leftrightarrow\frac{12}{13}x=2\Leftrightarrow x=\frac{13}{6}\)
mik ko chép lại đề, mik làm luôn:
a) x - \(\frac{31}{36}=\frac{-13}{38}\)
x = \(\frac{-13}{18}+\frac{31}{36}\)
\(x=\frac{5}{36}\)
b)\(2-x-\frac{3}{7}=\frac{9}{-21}\)
\(\frac{11}{7}-x=\frac{3}{7}\)
x = \(\frac{11}{7}-\frac{3}{7}\)
x = 8/7
c) x + 3/11 = 23/44
x = 23/44 - 3/11
x = 1/4
d) \(\frac{1}{12}-x=\frac{-11}{9}\)
x = \(\frac{1}{12}+\frac{11}{9}\)
x = 47/36
e) \(x-\frac{2}{3}=\frac{-17}{3}\)
x= -17/3 + 2/3
x = -5
f) \(x-\frac{1}{2}=\frac{11}{4}.\frac{3}{11}\)
x - 1/2 = 3/4
x = 3/4 + 1/2
x = 5/4
g) \(2x+\frac{3}{8}=\frac{-21}{32}.\frac{4}{7}\)
2x + 3/8 = -3 / 8
2x = -3/8 - 3/8
2x = -9/8
x = -9/8.1/2
x = -9/16
h) x - \(\frac{x}{3}=\frac{3}{57}.\frac{19}{12}\)
x - \(\frac{x}{3}=\frac{1}{12}\)
x = \(\frac{1}{12}+\frac{x}{3}\)
x = \(\frac{1+4x}{12}\)
=> 12x = 1+4x
12x - 4x = 1
8x = 1
x = 1/8
\(a/\frac{7}{9}-\frac{x}{3}=\frac{1}{9}\)
\(\Rightarrow\frac{x}{3}=\frac{7}{9}-\frac{1}{9}\)
\(\Rightarrow\frac{x}{3}=\frac{2}{3}\)
\(\Rightarrow x=2\)
Vậy \(x=2\)
\(b/\frac{1}{x}-\frac{-2}{15}=\frac{7}{15}\)
\(\Rightarrow\frac{1}{x}=\frac{7}{15}+\frac{-2}{15}\)
\(\Rightarrow\frac{1}{x}=\frac{1}{3}\)
\(\Rightarrow x=3\)
Vậy \(x=3\)
\(c/\frac{-11}{14}-\frac{-4}{x}=\frac{-3}{14}\)
\(\Rightarrow\frac{-4}{x}=\frac{-11}{14}-\frac{-3}{14}\)
\(\Rightarrow\frac{-4}{x}=\frac{-4}{7}\)
\(\Rightarrow x=7\)
Vậy \(x=7\)
\(d/\frac{x}{21}-\frac{2}{3}=\frac{5}{21}\)
\(\Rightarrow\frac{x}{21}=\frac{5}{21}+\frac{2}{3}\)
\(\Rightarrow\frac{x}{21}=\frac{19}{21}\)
\(\Rightarrow x=19\)
Vậy \(x=19\)
#Mạt Mạt#
a)\(\left(\frac{3}{29}-\frac{1}{5}\right)\cdot\frac{29}{3}\)
\(=\left(\frac{3}{29}\cdot\frac{29}{3}\right)-\left(\frac{1}{5}\cdot\frac{29}{3}\right)\)
\(=1-\frac{29}{15}\)
\(=\frac{-14}{15}\)
b)\(\frac{16}{15}\cdot\frac{-5}{14}\cdot\frac{54}{24}\cdot\frac{56}{21}\)
=\(=\frac{16\cdot\left(-5\right)\cdot54\cdot56}{15\cdot14\cdot24\cdot21}\)
\(=\frac{2^4\cdot\left(-5\right)\cdot2\cdot3^3\cdot2^3\cdot7}{3\cdot5\cdot7\cdot2\cdot2^3\cdot3\cdot7}\)
\(=2^4\)
c)\(\frac{37}{7}\cdot\frac{8}{11}+\frac{37}{7}\cdot\frac{5}{11}-\frac{37}{7}\cdot\frac{2}{11}\)
\(=\frac{37}{7}\cdot\left(\frac{8}{11}+\frac{5}{11}-\frac{2}{11}\right)\)
\(=\frac{37}{7}\cdot1\)
\(=\frac{37}{7}\)
Đúng nhớ k nhen!
a)\(\frac{5}{21}\)+\(\frac{-3}{7}\)<\(\frac{x}{21}\)<\(\frac{-2}{7}\)+\(\frac{8}{21}\)
\(\Rightarrow\)\(\frac{-4}{21}\)<\(\frac{x}{21}\)<\(\frac{2}{21}\)
\(\Rightarrow\)\(\frac{x}{21}\)\(\in\)\(\left\{\frac{-3}{21};\frac{-2}{21};\frac{-1}{21};\frac{0}{21};\frac{1}{21}\right\}\)
vậy x\(\in\)\(\left\{-3;-2;-1;0;1\right\}\)
Ta có:
\(\frac{2}{7}x-\frac{1-x}{3}=\frac{-11}{21}\)
\(\frac{2}{7}x-\left(\frac{1}{3}-\frac{1}{3}x\right)=\frac{-11}{21}\)
\(\frac{2}{7}x+\frac{1}{3}x-\frac{1}{3}=-\frac{11}{21}\)
\(\left(\frac{6}{21}+\frac{7}{21}\right)x=-\frac{11}{21}+\frac{7}{21}\)
\(\frac{13}{21}x=-\frac{4}{21}\)
\(x=-\frac{4}{21}:\frac{13}{21}=-\frac{4}{21}.\frac{21}{13}=-\frac{4}{13}\)
Vậy \(x=-\frac{4}{13}\)
\(\frac{2}{7}x-\frac{1-x}{3}=\frac{-11}{21}\Leftrightarrow6x-7+7x=-11\Leftrightarrow13x=-4\Leftrightarrow x=\frac{-4}{13}\)